Political And Philosophical Foundations of the Concept of the Social State and the Rule of Law and Their Development in Uzbekistan - Sirоjbеk Sultаnоv (Scientific Trends, 2025)
This article analyzes the philosophical roots of the concepts of the social state and the rule of law, the process of their formation and development, as well as the development of these ideas in Uzbekistan in harmony with national traditions, democratic values, and international standards. The article highlights the current aspects of the social and legal state in the context of historical sources, world experience, and current reforms.
Keywords: Social state, rule of law, political philosophy, democracy, human rights, Uzbekistan, Constitution, justice.